(untitled) (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive discussion of a pressing issue in translation studies: the manifestation of the translator’s professional mastery in literary translation and its significance. The study primarily analyzes the challenges of accurately and adequately conveying the author’s individual style, elements of national identity, and the spirit of the era in the translation process. Using comparative examples, the research examines the imagery and artistic devices characteristic of literary texts, as well as the specific features of their rendering in translation. Special attention is given to the translator’s skill in word choice and the role of lexical selection in ensuring the semantic and stylistic integrity of the work. These analyses highlight the translator’s depth of understanding of the literary text and their responsibility in conveying the spirit of the original..